Emerging Factors of Communicative Language Teaching (CLT) and Its Application in Indonesian English as a Foreign Language (EFL) Classrooms - Abd Rahman (Institut Agama Islam Negeri (IAIN) Kendari, 2017)
Communicative Language Teaching (CLT) has been adopted in many countries and has influenced the foreign and second language learning and teaching. This article aims to explore the emerging factors of CLT and how CLT is practiced in Indonesian EFL classroom. This study finds that there are three main phases of the development of CLT. Started from the works of Hymes (1967, 1972), Canale and Swain (1980) and Bachman (1990). Moreover, recent theories in second language acquisition and globalization are two main factors which lead to the widespread of CLT. Finally, in the EFL context the application of CLT has faced many challenges. Socio-cultures, grammar and reading-based exam, and teachers’ low English proficiency make the application of CLT in Indonesian EFL classroom has not reached its objectives yet.